Childbearing in Timor-Leste : beliefs, practices and issues : a thesis presented in fulfilment of the requirements for the degree of Master of Philosophy in Development Studies, Massey University - Thomas, Bronwyn (Massey University, 2005)
Timor-Leste is country with a past, a past that reveals considerable strength and a will to achieve the right to be self determining. It is also a country that will need development assistance for many years to come. Lack of development by Portugal, the former colonial power, compounded by an illegal and destructive occupation by Indonesia it was a country largely devoid of infrastructure at the time of independence in 2002. The population of this small half island is diverse, ethnically and linguistically. The population is considered to be amongst the poorest in the world and women's health, particularly the high maternal mortality rates and the issue of domestic violence have been identified as key areas for development. Women's marginal status in Timorese society is due to traditional and patriarchal practices which enable males to exert control and power over women in many facets of daily life. One of the numerous results of this is that women have reduced access to valued resources including health, education and food. Children are greatly valued, but the high fertility and maternal mortality rates has led the government to identify reproductive health as a high priority. Childbirth is only one aspect of reproductive health but it has traditionally received greater attention. Utilising qualitative research a small group of rural women shared their experiences and practices of childbearing. One aspect the women identified was a lack of information as childbirth is a taboo subject until a woman becomes a mother. In view of this and the numerous priorities identified by Timorese government for future work, including the mainstreaming of gender health concerns I consider the research findings. Due to the need for cost effective and sustainable programmes I recommend Adolescent Sexual Reproductive Health (ASRH) as an area for future exploration and consideration. This is an area found to be commonly overlooked in development activities, but can have many positive outcomes. A broad ASRH programme could address not only the issues of poor information but also work toward challenging gender norms and values which are key influences on women's reproductive health and childbearing experiences. ASRH may be controversial, but some consider programmes can be implemented as early as ten years of age. As adolescents are the next generation of parents and the most receptive to change they are the ideal target group for the future health of this country.
Keywords: East Timor; Childbirth; Women; Women's health services